(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the analysis of psychologism and the reflection of the specifics of the national mentality, particularly the psychological analysis in Uzbek literature of the 20th century. Since the emergence of this method — from the 19th century to the present day — debates have not ceased regarding its effectiveness, forms of realization, and limitations. It also highlights the need for a deeper understanding of the national specifics of psychological prose and the transformations that the techniques of psychologism undergo when functioning in different cultural contexts.The focus is placed on the development of the inner world of characters, the use of techniques such as inner monologue and psychological portrait as means of revealing the psycho-emotional state of the protagonists. The novella Shaytanat by Tohir Malik is analyzed, and an attempt is made to systematize the methods of psychologism in Uzbek literature of the 20th century.Special attention is given to the influence of global literary movements such as modernism and existentialism on the formation of Uzbek literary psychologism. The results of the study contribute to the understanding of the relationship between literary psychologism and national identity. It is important to note that the psychologism of both authors is not limited to a simple reproduction of national stereotypes. Tohir Malik creates complex, multidimensional characters who, while representing the national mentality, also transcend national typification and acquire a universal, human significance.